Organizational and Technological Aspects of the Creation and Operation of Ostrich Farms - Babayeva Shaxlo Aliyevna; Mamatova Ozoda (American Journal of Biomedicine and Pharmacy, 2026)
This article examines the main organizational and technological approaches to the establishment and operation of ostrich farms. Various models for farm development are analyzed, including egg incubation, rearing of young birds, fattening of birds, and breeding stock. The economic aspects of ostrich farming, cost structure, and factors influencing production profitability are presented. Particular attention is paid to the biological and behavioral characteristics of the African ostrich, the impact of stress factors on productivity, and the requirements for poultry husbandry. It is shown that the greatest economic efficiency is achieved by selling young birds aged 1 to 6 months, strictly adhering to technological and sanitary standards